(3cTa GdGSJGQ Yf Yde MQha GdZHGQs - (3GHf eMeO Hf Ydj GdbQTi GdbdUGhis; (3YHO Gddg Hf LYaQ HGYdhj Gdjefjs
(3ChdgG (B:s
(3CeG HYO agPG fHPg cGajg TGajg EbJWaJNG ef cJGH GdeSei jcTa GdLdHGH Yf YGde GdMSGH dJchf Zfjg dHYV GdWdGH hSejJgG HcTa GdGSfGQ Yf Yde MQha GdZHGQ s
(3GdfSNI HgG MhGTs
(3cTa GdLdHGH Yf Yde GdMSGH GfXQ EjVGM Gdecfhf L(B2 (3U` (B358s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdNRGfI GdYeg HGdQHGW (B_ (3GdeZQH (B(358) s
Keywords: (3GdQjGVjGJs